Pregnancy outcome in Charcot–Marie–Tooth disease: results of the CMT‐NET cohort study in Germany. (16th June 2020) - Rudnik‐Schöneborn, S.; Thiele, S.; Walter, M. C.; Reinecke, L.; Sereda, M.; Schöneborn, R.; Elbracht, M.
Abstract : Background and purpose: Systematic research on the effect of Charcot–Marie–Tooth (CMT) disease on the outcome of pregnancy and conversely the effect of pregnancy on neuropathy is still sparse. Methods: A clinical cohort study and cross‐sectional study within the German CMT‐NET was conducted between 2016 and 2019. Inclusion criteria were a confirmed diagnosis of CMT and at least one completed pregnancy after 1990. All participants agreed to fill in questionnaires and have their medical files reviewed. Results: The study group comprised 54 women with a total of 98 pregnancies. The mean age at onset of CMT disease was 12.6 years (range 0–37 years). Fifty (92%) patients had autosomal dominant CMT; two patients each (4%) had X‐linked and autosomal recessive CMT. Forty patients (74%) had a PMP22 gene duplication (CMT1A). Obstetric complications did not differ significantly from a German reference population, neither in the whole group nor in the CMT1A group. Overall there was no increased newborn morbidity and mortality. About one‐third of patients reported exacerbation of CMT disease in or after pregnancy. No adverse effects of anaesthesia were reported. Most participants stressed a positive attitude and awareness of challenges associated with pregnancy. Important issues were assistance and support in caring for the family. Discussion: In line with findings from our previous study undertaken in the 1990s, there were no increased complication rates for pregnancy and delivery. These results are reassuring for the vast majority of CMT patients and are important for family planning and clinical care.